Influence of spirituality and prosocial behaviour on psychosocial functioning among international students the midst of Covid-19 - Ariff, Nor Balqis; Ab Razak, Ratna Roshida (Human Resource Management Academic Research Society, 2022)
This study is an attempt to examine the relationship between spirituality and prosocial behaviour with psychosocial functioning among international students of Universiti Putra Malaysia (UPM). By using snowball sampling technique, a total of 202 respondents were obtained. The Spirituality Scale (SS) was the chosen instrument to measure spirituality, Prosocialness Scale for Adults (PSA) will measure prosocial behaviour and the Inventory Psychosocial Functioning (IPF) Scale by Marx will measure psychosocial functioning. The result revealed that most of the respondents had high level of spirituality (78.2%) and prosocial behaviour (88.6%), whereas a moderate level for psychosocial functioning (65.8%). Moreover, the result from the Mann-Whitney U Test showed that there are no significant differences in psychosocial functioning between male and female. Using the Spearman’s Rank Correlation Test, spirituality was significantly correlated with all aspects of psychosocial functioning such as family (r=0.215, p<0.05), friendships and socializing (r=0.334, p<0.05), education (r=0.286, p<0.05) and self-care (r=0.224, p<0.05). Variable such as prosocial behaviour was also significantly correlated with psychosocial functioning in family (r=0.165, p>0.05), friendships and socializing (r=0.290, p>0.05), education (r=0.249, p>0.05) and self-care (r=0.163, p>0.05). This study concluded that the international students’ spirituality and prosocial behaviour were important in influencing the level of their psychosocial functioning.